2014
DOI: 10.1016/j.euroneuro.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine dose-dependently reverses 5-HT depletion-induced deficits in spatial working and object recognition memory: A potential role for 5-HT1A receptor agonism and 5-HT3 receptor antagonism

Abstract: We previously reported that the investigational multimodal antidepressant, vortioxetine, reversed 5-HT depletion-induced memory deficits while escitalopram and duloxetine did not. The present report studied the effects of vortioxetine and the potential impact of its 5-HT1A receptor agonist and 5-HT3 receptor antagonist properties on 5-HT depletion-induced memory deficits. Recognition and spatial working memory were assessed in the object recognition (OR) and Y-maze spontaneous alternation (SA) tests, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 47 publications
5
94
1
4
Order By: Relevance
“…In several studies, rats were treated with a tryptophan hydroxylase inhibitor in order to deplete central 5-HT and consequently impair cognition. Vortioxetine demonstrated a reversal of this induced impairment in rats as assessed by the novel object recognition and Y-maze spontaneous alteration (spatial memory) tests [33,34]. The SSRI escitalopram and SNRI duloxetine, however, did not reverse any deficits [34].…”
Section: Efficacy Results --Pro-cognitive Effects In Preclinical Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…In several studies, rats were treated with a tryptophan hydroxylase inhibitor in order to deplete central 5-HT and consequently impair cognition. Vortioxetine demonstrated a reversal of this induced impairment in rats as assessed by the novel object recognition and Y-maze spontaneous alteration (spatial memory) tests [33,34]. The SSRI escitalopram and SNRI duloxetine, however, did not reverse any deficits [34].…”
Section: Efficacy Results --Pro-cognitive Effects In Preclinical Modelsmentioning
confidence: 92%
“…The SSRI escitalopram and SNRI duloxetine, however, did not reverse any deficits [34]. Further, the beneficial effects in the object recognition task were maintained with chronic vortioxetine administration, but no improvement was noted in performance in the spontaneous alternation test [33]. With acute and subchronic vortioxetine administration, Wallace et al also showed reversal of induced cognitive impairment in rats using the attentional set-shifting test as a measure of reversal learning [35].…”
Section: Efficacy Results --Pro-cognitive Effects In Preclinical Modelsmentioning
confidence: 99%
“…Para comprovar este pressuposto Du Jardin et al 27 realizaram um estudo em ratos adultos utilizando a paraclorofenilalanina, composto capaz de inibir o triptofano hidroxilase e por conseguinte diminuir a síntese de 5-HT. Com a redução do triptofano foi possível verificar que houve depleção da serotonina, observadas pelas alterações no teste de memória espacial no labirinto-Y e no reconhecimento de objetos.…”
Section: Discussionunclassified
“…Para a analgesia foi utilizado o cloridrato de tramadol na dose de 10 mg/kg diluído em 50ml de água, a cada 12 horas, por via oral, durante 7 dias 21 . Os animais ficaram em repouso por cinco dias e após esta data foram novamente anestesiados e levados ao estereotáxico onde receberam o peptídeo Beta-Amiloide [25][26][27][28][29][30][31][32][33][34][35] (Sigma-Aldrich) através de seringa de Hamilton na região hipocampica de CA1 conforme descrito por Freir, Costello e Herron 22 .…”
Section: Cirurgia Experimentalunclassified
“…Ex vivo autoradiography data were quantified as described previously (du Jardin et al, 2014). Results are expressed as mean 6 S.E.M.…”
Section: Ex Vivo Binding To R5-ht 1a and R5-ht 7 Receptors In Rat Brainmentioning
confidence: 99%